Nanosilk Increases the Strength of Diabetic Skin and Delivers CNP-miR146a to Improve Wound Healing - Niemiec, Stephen M.; Louiselle, Amanda E.; Hilton, Sarah A.; Dewberry, Lindel C.; Zhang, Liping; Azeltine, Mark; Xu, Junwang; Singh, Sushant; Sakthivel, Tamil S.; Seal, Sudipta; Liechty, Kenneth W.; Zgheib, Carlos (Frontiers in Immunology, 2020)
Diabetes mellitus is a metabolic disorder associated with properties and an increased risk of chronic wounds due to sustained pro-inflammatory response. We have previously of radical scavenging cerium oxide nanoparticles (CNP) conjugated to the anti-inflammatory microRNA (miR)-146a, termed CNP-miR146a, improves diabetic wound healing by synergistically lowering oxidative stress and inflammation, and we sought to evaluate this treatment in a topical application. Silk fibroin is a biocompatible polymer that can be fabricated into nanostructures, termed nanosilk. Nanosilk is characterized by a high strength-to-density ratio and an ability to exhibit strain hardening. We therefore hypothesized that nanosilk would strengthen the biomechanical properties of diabetic skin and that nanosilk solution could effectively deliver CNP-miR146a to improve diabetic wound healing. The ability of nanosilk to deliver CNP-miR146a to murine diabetic wounds and improve healing was assessed by the rate of wound closure and inflammatory gene expression, as well as histologic analysis. The effect of nanosilk on the properties of human diabetic skin was evaluated by testing the biomechanical properties following topical application of a 7% nanosilk solution. Diabetic murine wounds treated with topical nanosilk and CNP-miR146a healed by day 14.5 compared to day 16.8 in controls (p = 0.0321). Wounds treated with CNP-miR146a had higher collagen levels than controls (p = 0.0126) with higher pro-fibrotic gene expression of TGFβ-1 (p = 0.0092), Col3α1 (p = 0.0369), and Col1α2 (p = 0.0454). Treatment with CNP-miR146a lowered pro-inflammatory gene expression of IL-6 (p = 0.0488) and IL-8 (p = 0.0009). Treatment of human diabetic skin with 7% nanosilk solution resulted in significant improvement in maximum load and modulus (p < 0.05). Nanosilk solution is able to strengthen the biomechanical properties of diabetic skin and can successfully deliver CNP-miR146a to improve diabetic wound healing through inhibition of pro-inflammatory gene signaling and promotion of pro-fibrotic processes.